Hyperbaric oxygen therapy: future prospects in regenerative therapy and anti-aging - Gupta, Manoj; Rathored, Jaishriram (Frontiers in Aging, 2024)
Hyperbaric Oxygen Therapy (HBOT) utilizes 100% oxygen at high atmospheric pressure for clinical applications. HBOT has proven to be an effective supplementary treatment for a variety of clinical and pathological disorders. HBOT's therapeutic results are based on the physiological effects of increased tissue oxygenation, or improved oxygen bioavailability. HBOT's current indications in illnesses like as wound healing, thermal or radiation burns, and tissue necrosis point to its function in facilitating the regeneration process. Various research has revealed that HBOT plays a function in vascularization, angiogenesis, and collagen production augmentation. Individual regeneration capacity is influenced by both environmental and genetic factors. Furthermore, the regenerating ability of different types of tissues varies, and this ability declines with age. HBOT affects physiological processes at the genetic level by altering gene expression, delaying cell senescence, and assisting in telomere length enhancement. The positive results in a variety of indications, ranging from tissue regeneration to better cognitive function, indicate that it has enormous potential in regenerative and anti-aging therapy.